2019
DOI: 10.21325/jotags.2019.512
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and New Product Development: Delving into Food and Beverage Managers Perspectives

Abstract: In order to survive in a competitive environment and make sustainable profits, hotel businesses must be different for competitive advantage and innovation. When the literature on innovation in hotel establishments is examined, it is seen that the studies reflecting the views of food and beverage managers are insufficient. The aim of this study is to reveal the perspectives of food and beverage managers about innovation and new product development processes in 4 and 5 star hotels in Antalya. For this purpose, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The importance given to the development of pro-environmental products and services in accommodation businesses is increasing day by day. At this point, hotel employees' ideas and creativity are needed (Uygur et al, 2019). Research on organizational behaviour has revealed that OCB has a positive relationship with employees' creativity.…”
Section: Effects Of Green Organizational Citizenshipmentioning
confidence: 99%
“…The importance given to the development of pro-environmental products and services in accommodation businesses is increasing day by day. At this point, hotel employees' ideas and creativity are needed (Uygur et al, 2019). Research on organizational behaviour has revealed that OCB has a positive relationship with employees' creativity.…”
Section: Effects Of Green Organizational Citizenshipmentioning
confidence: 99%
“…It is useful to examine the innovation understandings and practices in accommodation establishments Zopiatis & Theocharous, 2018). Although studies have been carried out on this subject (Gomezelj, 2016;Martin-Rios & Pasamar, 2018), it is a necessity to examine innovative ideas and solutions in this regard (Nicolau & Santa-Maria, 2013;Zopiatis & Theocharous, 2018;Uygur et al, 2019;Luu, 2019;De Larrea et al, 2021;Lim & Ok, 2021;Shin & Perdue, 2022). In this study, the idea of a "Fixed iPad" is proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is useful to examine the innovation understandings and practices in accommodation businesses Zopiatis & Theocharous, 2018). Although the literature supports that there are studies on the concept of innovation in accommodation businesses (Martin-Rios & Ciobanu, 2019;Gomezelj, 2016;Martin-Rios & Pasamar, 2018), it is a necessity to examine innovative ideas and solutions in this regard (Nicolau & Santa-Maria, 2013;Zopiatis & Theocharous, 2018;Uygur et al, 2019;Luu, 2019;De Larrea et al, 2021;Lim & Ok, 2021;Shin & Perdue, 2022). In this study "Fixed iPad" technology is proposed as an innovative idea in chain accommodation businesses.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to developments in information and communication technologies, customers are also affected by innovative changes (Uygur et al, 2019). Adapting a new idea to organizational activities and as a result, increasing corporate efficiency and effectiveness can be associated with innovation (Küçük, 2017;Hitt et al, 2005;Arslan, 2001).…”
Section: Introductionmentioning
confidence: 99%